Grievance Mechanism and Legal Dispute Resolution for Medical Personnel and Patients - Widjaja, Gunawan (International Journal of Social Science, Education, Communication and Economics, 2025)
Complaints and legal dispute resolution mechanisms between medical personnel and patients are important processes in safeguarding patients' rights while ensuring that medical personnel carry out their profession with applicable standards. Complaints are usually made by patients or families to the relevant institutions, where the process may involve mediation as an initial attempt at resolution. If mediation is unsuccessful, the dispute may proceed through formal legal channels or alternative mechanisms such as arbitration. Settlements are based on evidence, medical documentation, and expert opinion to ensure fair decisions. This mechanism is designed to create transparency, accountability, and legal protection that helps build trust between patients and medical personnel and maintain the quality of healthcare services.